The prediction of preterm delivery: What is new?. Issue 1 (February 2019) - Suff, Natalie; Story, Lisa; Shennan, Andrew
Abstract: Preterm birth, defined as birth occurring prior to 37 weeks gestation, is a serious obstetric problem accounting for 11% of pregnancies worldwide. It is associated with significant neonatal morbidity and mortality. Predictive tests for preterm birth are incredibly important, given the huge personal, economic, and health impacts of preterm birth. They can provide reassurance for women who are unlikely to deliver early, but they are also important for highlighting those women at higher risk of premature delivery so that we can offer prophylactic interventions and help guide antenatal management decisions. Unfortunately, there is unlikely to be a single test for predicting preterm birth, but a combination of tests is likely to improve clinical prediction. This review explores the clinical utility of the currently marketed predictive tests for preterm birth in both singleton and multiple pregnancies, as well as discussing novel predictive tests that may be useful in the future.